Islam di Indonesia : Dari Little ke Greater Traditions - Fauzan Saleh (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2003)
Islam came to Indonesia when it was considerably weak either in politic, economic or military aspects. Consequently, the early presence of Islam in this country could not directly transform the whole belief systems that are irreconcilable to its principal tenets. Islam could only penetrate into the country's cultural life through assimilation, not revolution. However, like other religions in general, Islam is always in flux. Islam is also subject to historical progress, in the sense that is evolving from